Thea Stilton and the tropical treasure - Stilton, Thea; Cairoli, Valeria; Verzini, Daniele; Pellizzari, Barbara; Balleello, Chiara; Clement, Emily (New York, NY : Scholastic Inc., 2015)
While on vacation in the Bahamas, the Thea sisters stumble across an old pirate map and endeavor to find the treasure, unaware that someone else is also seeking the prize.
Translated from the Italian.
Keywords: Stilton, Thea -- Juvenile fiction; Stilton, Thea -- Fiction; Stilton, Thea; Mice -- Juvenile fiction; Treasure troves -- Juvenile fiction; Sisters -- Juvenile fiction; Mice -- Fiction; Buried treasure -- Fiction; Maps -- Fiction; Sisters -- Fiction; Mystery and detective stories; Mice; Sisters; Treasure troves; Bahamas -- Juvenile fiction; Bahamas -- Fiction; Bahamas; Fiction; Juvenile works